Supply Chain Key Success Factors for Organic Agricultural Products: Case Study in Taiwan - Ching-Chiao Yang; PO-LIN LAI; Ying Li; Yin-Yu Hsu (International Journal of Supply Chain Management, 2018)
The Analytic Hierarchy Process (AHP) method is employed to evaluate the significance of various criteria influencing development of the organic agricultural products supply chain in Taiwan. A three-level hierarchical structure with four dimensions and 19 criteria was proposed based on literature review and personal interviews. Sourcing results from an AHP survey indicates that policies and laws are perceived as the most crucial factors influencing development of the organic agricultural products supply chain in Taiwan, followed by manufacturing capability, marketing capability, and logistics capability. Overall, results indicate that the five most critical criteria influencing development of the organic agricultural products supply chain in Taiwan are organic agricultural products approval and certification, capital acquiring, improving cultivated skills, establish stable system of distribution, and transparent and reasonable pricing. It is important to note that government and related authorities also put more effort in temperature control and post-harvest handling. Therefore, logistics capability is also a critical factor influencing development of the organic agricultural products supply chain in Taiwan whereas few previous studies have discussed this issue.